Engineered acetoacetate‐inducible whole‐cell biosensors based on the AtoSC two‐component system. Issue 11 (9th August 2021) - Rutter, Jack W.; Dekker, Linda; Fedorec, Alex J. H.; Gonzales, David T.; Wen, Ke Yan; Tanner, Lewis E. S.; Donovan, Emma; Ozdemir, Tanel; Thomas, Geraint M.; Barnes, Chris P.
Abstract: Whole‐cell biosensors hold potential in a variety of industrial, medical, and environmental applications. These biosensors can be constructed through the repurposing of bacterial sensing mechanisms, including the common two‐component system (TCS). Here we report on the construction of a range of novel biosensors that are sensitive to acetoacetate, a molecule that plays a number of roles in human health and biology. These biosensors are based on the AtoSC TCS. An ordinary differential equation model to describe the action of the AtoSC TCS was developed and sensitivity analysis of this model used to help inform biosensor design. The final collection of biosensors constructed displayed a range of switching behaviours at physiologically relevant acetoacetate concentrations and can operate in several Escherichia coli host strains. It is envisaged that these biosensor strains will offer an alternative to currently available commercial strip tests and, in future, may be adopted for more complex in vivo or industrial monitoring applications. Abstract : Rutter and coworkers engineer a range of acetoacetate sensitive whole‐cell biosensors, based on the AtoSC two‐component system. A modelling and sensitivity analysis approach is applied to identify factors that are important in determining the response of these biosensors. The important factors are then varied to construct an array of acetoacetate biosensors, which display diverse switching behaviours.